THE RULE OF LAW FOR CRIMINAL DEFAMATION OF PRODUCT REVIEWS ON SOCIAL MEDIA - Aulia Rahman Hakim Hasibuan; Indra Utama Tanjung; Kharisma Preety Queen Cindai Br Panjaitan (PT. Sinergi Legal Publisher, 2024)
With the development of technological advances in economic activities and electronic commerce, it can create a loophole for criminal defamation of a product that is given a review or assessment by its consumers. The problem is whether the reviews are true based on the facts perceived by consumers of the product or deliberately to provide negative reviews in order to drop the selling value of the product. The Criminal Code regulates the criminal offence of defamation in Article 310 paragraph (1) and 310 paragraph (2). In its development, the criminal offence of defamation committed through electronic media is also regulated in Article 27 paragraph (3) of the Electronic Information and Transaction Law. The purpose of this research is to find out the legal regulation of criminal defamation of a product on social media based on positive law in Indonesia, and to find out how a review can be said to be a criminal defamation. This research is included in descriptive research with the type of normative juridical research, which uses data sources from secondary data, then the analysis method is qualitative analysis. The legal regulation of criminal defamation of a product review on social media based in Indonesia is regulated in Article 27 paragraph (3) Jo. Article 27 Paragraph (3) of the Law of the Republic of Indonesia Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. Forms of actions that can be considered as defamation through product reviews on social media include if someone deliberately spreads false information or spreads slander about products or producers on social media.